Virtual Learning Environments: methodological resources in the development of lasting learning - Figueroa Moreira , Yelania Paola; Navarro Ponce , John Jairo (Revista Minerva, 2022)
From a perspective of current education at a global level, technology can be mentioned as a fundamental basis in promoting innovation and transformation of educational processes, so the objective of this work is to compile information on how these environments virtual learning which have become necessary strategies not only for the student but also for the teacher, they can achieve a relevant form of teaching and above all promote the obtaining of that lasting learning that must be conceived in the classrooms, whether they are in a face-to-face or virtual system. The methodology applied in this study is based on a bibliographical research which is supported by the theoretical foundations based on previous studies carried out by contemporary authors who have expressed their position on the variables of this article and their importance in education indefinitely. It is concluded that the comprehensive training of students can be promoted through these virtual learning environments and thus promote lasting learning supported by technological resources that enable this process.